A new typology of pocket parks: inspiring small spaces for changing cities. Issue 3 (8th June 2020) - Babalis, Dimitra
Abstract : The contemporary city has witnessed sweeping changes in terms of structure and image. New glittering globalised urban forms emerged, however, associated 'anywhere' contemporary urban spaces are often criticised as bland and meaningless. The global crisis of 2008 brought with it a heightened realisation of the need to manage cities differently and more sustainably. In recent decades, the concept of a public space/garden has changed from something largely ornamental and often to be viewed 'passively' to creating spaces for 'active engagement' as well as, relaxation and socialisation, and with resultant positive impacts on community health and well-being. Small spaces have the potential to bring people together to create places of community cohesion, but they may also hold the key to addressing broader issues such as increasing biodiversity and repairing environmental damage. This study of pocket parks suggests that 13 distinct 'types' of pocket park have emerged since they were first identified as a special kind of urban space in the late 1960s. They now possess a wide range of spatial configurations and perform a variety of functions. However, these new possibilities need a variety of skills and knowledge to exploit them to their full potential and in pocket park creation.